2019
DOI: 10.1186/s12879-019-4468-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial co-infection of the respiratory tract in ventilated children with bronchiolitis; a retrospective cohort study

Abstract: BackgroundViral bronchiolitis is the most common cause of respiratory failure requiring invasive ventilation in young children. Bacterial co-infections may complicate and prolong paediatric intensive care unit (PICU) stay. Data on prevalence, type of pathogens and its association with disease severity are limited though. These data are especially important as bacterial co-infections may be treated using antibiotics and could reduce disease severity and duration of PICU stay. We investigated prevalence of bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 19 publications
5
46
2
2
Order By: Relevance
“…Concerning risk factors, we highlighted a significant association between bacterial co-infection and development of PARDS in our study cohort. This has also been shown in previous studies which have shown an association between bacterial co-infection, severe respiratory disease, and longer PICU stay [ 21 ]. None of the previous studies has demonstrated the association between bacterial co-infection and PARDS in AVB.…”
Section: Discussionsupporting
confidence: 85%
“…Concerning risk factors, we highlighted a significant association between bacterial co-infection and development of PARDS in our study cohort. This has also been shown in previous studies which have shown an association between bacterial co-infection, severe respiratory disease, and longer PICU stay [ 21 ]. None of the previous studies has demonstrated the association between bacterial co-infection and PARDS in AVB.…”
Section: Discussionsupporting
confidence: 85%
“…In the literature, bacterial co-infection rates range from 16% to 37%, with higher rates determined in the PICU. 30,31 Similar to our study, bacterial co-infection with typical organisms, such as Moraxella Catarrhalis, and Haemophilus Influenzae, have been reported in previous studies focused on patients in the PICU. 30,31 In previous studies, multiple viral infection rate is reported to be between 31 and 37%.…”
Section: Article In Presssupporting
confidence: 88%
“…30,31 Similar to our study, bacterial co-infection with typical organisms, such as Moraxella Catarrhalis, and Haemophilus Influenzae, have been reported in previous studies focused on patients in the PICU. 30,31 In previous studies, multiple viral infection rate is reported to be between 31 and 37%. 32,33 Recent studies found hRV, RSV and AdV as the leading viruses in multiple infections.…”
Section: Article In Presssupporting
confidence: 88%
“…those infants ill enough to require intubation. [33,34]. Infants who are less ill are generally assumed to have only the virus and antibiotics are generally withheld; because such children are not intubated comparable data regarding bacteria in the lung are not available.…”
Section: Plos Onementioning
confidence: 99%